1968
DOI: 10.1111/j.1365-2133.1968.tb12298.x
|View full text |Cite
|
Sign up to set email alerts
|

Vitiligo in Mature-Onset Diabetes Mellitus

Abstract: A study has been made on the incidence of vitiligo in matureonset diabetics attending hospital.An increased incidence of vitiligo was found in the whole group of diabetics, and in the female diabetics, when compared with controls.In more than half the patients with both vitiligo and diabetes, the vitiligo preceded the diabetes.Vitiligo begins before the age of 40 in over 80% of all cases but did so in only 24% of 25 diabetics with vitiligo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
1
2

Year Published

1970
1970
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(28 citation statements)
references
References 6 publications
(3 reference statements)
2
23
1
2
Order By: Relevance
“…There is evidence suggesting that vitiligo is an autoimmune disease: (1) high frequency of the association with other autoimmune diseases, such as thyroid diseases, pernicious anemia and diabetes mellitus [1,4,5,9,15]; (2) high incidence of various autoantibodies in sera [2][3][4]; (3) the presence of antimelanin antibodies in the sera [14].…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence suggesting that vitiligo is an autoimmune disease: (1) high frequency of the association with other autoimmune diseases, such as thyroid diseases, pernicious anemia and diabetes mellitus [1,4,5,9,15]; (2) high incidence of various autoantibodies in sera [2][3][4]; (3) the presence of antimelanin antibodies in the sera [14].…”
Section: Discussionmentioning
confidence: 99%
“…6,7 In our study we have evaluated for associated systemic illness which showed 8% of patient had diabetes mellitus, where similar results is seen in a study by Dauber et al One patient had hypothyroidism and one had hyperthyroidism when compared to 7 % cases were associated with graves diseases in a study. 8 Altar et al in a study on 192 vitiligo patients in the age group 6-60 years found that generalised type of vitiligo was present in 72.9%. Among patients with vitiligo, 84% were thyroid, 15% hypothyroid and 1% hyperthyroid which is comparable to our study.…”
Section: Discussionmentioning
confidence: 99%
“…Dawber et al found that 4.8% of diabetics had vitiligo 4.5% to 7.7% frequency of vitiligo has been reported in late onset of diabetes. 15 Hajini GH et al though associated with both insulin dependent and non insulin dependent types of diabetes, in most of patients it is seen after age of 40 years. 16 In present study 2% of total patients having vitiligo were observed and both of them were of above 40 years.…”
Section: Vitiligomentioning
confidence: 99%